Status Hukum Atas Tanah Yang Belum Bersertifikat Yang Sementara Disengketakan Oleh Ahli Waris dan Masyarakat Desa Tolitehuyu Kecamatan Monano Kabupaten Gorontalo Utara - Ferawati Potonuo; Nur Mohammad Kasim; Moh. Taufik Z. Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out the legal status of uncertified land that is disputed by the heirs and the community of Tolitehuyu village, Monano District, North Gorontalo Regency and to find out the form of legal settlement by the Tolitehuyu Village Government regarding disputed uncertified land. This research uses empirical methods. The results of this research show that the legal status of land ownership by the people of Tolitehuyu Village, Monano District, North Gorontalo Regency, some have a certificate and some do not have a certificate for the land they own. Where those who already have a legal status certificate are already the property of that community. Furthermore, for those who do not yet have a certificate, the legal status of their land is unclear or still weak. So the legal status must be registered with the National Land Agency of North Gorontalo Regency in accordance with the provisions of the applicable laws. The role of the Tolitehuyu Village Government in resolving uncertified land disputes in the community can be achieved by mediating through an intermediary called a modiator. The process of resolving land disputes by the Tolitehuyu Village Government is carried out in stages, namely submitting a complaint to the hamlet head, head The village presents the parties to the dispute, collects data, mediates and reads the decision.